Geography : realms, regions, and concepts - De Blij, Harm J., 1935-2014; Muller, Peter O., 1942- (New York : John Wiley & Sons, 2002)
This edition has been substantially updated to reflect happenings around the globe at the beginning of the 21st century. Physical geography is presented more consistently from chapter-to-chapter with major revisions to several chapters. A foldout map of the world in 1900 is included.
1. Resilient Europe: Confronting New Challenges. 2. Russia's Fractious Federation. 3. North America: The Postindustrial Transformation. 4. Middle America: Collision of Cultures. 5. South America: Continent of Contrasts. 6. North Africa/Southwest Asia: The Energy of Islam. 7. Subsaharan Africa: Realm of Reversals. 8. South Asia: Resurgent Regionalism. 9. East Asia: Realm of Titans; 10. Southeast Asia: Between the Giants. 11. Australia: Dilemmas Downunder. 12. The Pacific Realm.
Includes bibliographical references.
Keywords: Geography; Geografía